Creation, characterization, and assignment of opsonic values for a new pneumococcal OPA calibration serum panel (Ewha QC sera panel A) for 13 serotypes - Burton, Robert L. (Medicine (Baltimore), 2018)
Pneumococcal conjugate vaccines (PCVs) have been very effective in reducing the disease burden caused by Streptococcus pneumoniae serotypes covered by the current vaccine formulations. However, the incidence of disease caused by serotypes not covered by the vaccine is increasing. Consequently, there are active efforts to develop new PCVs with additional serotypes in order to provide protection against the emergent serotypes. Due to costs and ethical issues associated with performing true vaccine efficacy studies, new PCVs are being licensed based on their immunogenicity, which may be assessed with 2 in vitro assays: enzyme-linked immunosorbent assay (ELISA) for quantitating antibody level and opsonophagocytic assay (OPA) for assessing protective function. While a standardized ELISA has been developed, OPA results from different laboratories can be quite disparate, even among laboratories utilizing the same platform. In order to harmonize OPA data, a recent international collaboration assigned opsonic indices to the US Food and Drug Administration (US FDA) reference serum, 007sp, as well as a panel of US FDA calibration sera. However, due to a low number of aliquots, the availability of these calibration sera is extremely limited. Because calibration sera are critical to establish the performance characteristics of an OPA, a second calibration serum panel was created, comprised of 20 sera collected from adults immunized with the 23-valent polysaccharide vaccine, with 150 to 500 aliquots prepared for each serum. In order to establish consensus OPA values of the 20 sera for the 13 serotypes in 13-valent PCV, the sera were tested by 4 laboratories in an international collaborative OPA study. The 007sp results of 1 laboratory deviated significantly from those obtained by the other laboratories, as well as from previously assigned values. Due to these discrepancies, the consensus values for the calibration sera were determined based on the data from the remaining laboratories. Thus, we were able to create a panel of sera with consensus opsonic values that could be used by outside laboratories to calibrate pneumococcal OPAs. Our results also confirmed findings of a previous study that normalization of OPA results significantly reduces interlaboratory variation, with normalization based on 007sp reducing variation by 43% to 74%, depending on serotype.